Pensamientos de un violador en serie (2006)
The present article corresponds to a case study, in which the author describes material obtained by working directly with V.S.R., with the purpose of simultaneously illustrate the thoughts of a serial rapist and clarify some theoretical elements of psychopath. The document describes to V.S.R. like condemned man to 20 prison years by three accomplished violations, when he was 23 years and being in Reformation Center, he can return to prison or to be in the street with watched over freedom measure. The forensic psychologist's report is requested to the District Attorney's Office for its evaluation and orientation of the measure. Through the interviews and file analysis, we will be able to know the iterative sexual aggressor's true thoughts and pathology. Key words: sexual aggressor, psychopath, interview, thinking way.